THE JUSTIFICATION AND ILLEGITIMACY OF ESPIONAGE IN INTERNATIONAL LAW: A RESEARCH REVIEW - Khizar Hayat; Dr. Ahmad Hassan Khattak (Journal of Religion and Society, 2025)
Espionage, as a tool for gathering intelligence and influencing foreign policies, has long been a contentious issue in international law. This research review delves into the legal status of espionage, particularly in peacetime, and examines the arguments for and against its justification under international law. The study is divided into two main parts: the first explores the types of espionage, including covert operations and human intelligence, while the second analyzes the legal interpretations of espionage under international law, focusing on the United Nations Charter and other relevant conventions. The research highlights the evolving nature of state sovereignty and territorial integrity in the post-World War II era, which has significantly impacted the perception of espionage. While some legal experts argue that espionage is a necessary tool for national security and maintaining peace, others contend that it violates principles of non-intervention and territorial integrity. The study also addresses the emergence of cyber espionage, which has further complicated the legal landscape. The research concludes that while espionage is not explicitly prohibited under international law, its legitimacy remains a subject of debate, especially in the context of modern technological advancements. The paper calls for a more nuanced understanding of espionage within the framework of international law, considering both its historical context and contemporary challenges. Keywords: Espionage, International Law, Covert Operations, Cyber Espionage, Sovereignty, Non-Intervention, United Nations Charter